KUALITAS PELAYANAN DALAM UPAYA MENINGKATKAN KEPUASAN WISATAWAN THE LOSARI HOTEL KUTA DAN VILLAS - Ni Ketut Dwipayanti; Ni Nyoman Menuh (Forum Manajemen STIMI Handayani Denpasar, 2016)
This research aimed to know the level of tourist satisfaction showed by thequality of hotel services and to know the average level of tourist satisfaction ownedby The Losari Hotel Kuta and Villas. This researched applied on a technique ofsample taking, such as purpose sampling to gain an accurate data from respondents.Technique of collecting data was carried out through list of questionnaire orstructured written questions that had been passed on 54 respondents. Techniqueof analyzing data applied was descriptive quantitative. The indicator used in thisresearch was the promptness of check-in service, room sanitation, bed comfort, roomserenity, conditions of furnitures, TV channels, knowledges of all staff in serving theguests, accuracy in providing the guests’ needs, cleanliness of villa as in a whole,villa security and Butler service. It was found that the average rate of all componentsthat had been surveyed by the guests appeared on the criterion very satisfied. As anadditional, in order to increase the services in The Losari Hotel and Villa, there aresome suggestions proposed in terms of increasing the promptness of services, roomsanitation, bed comfort, including to replace and fix furnitures, also adding more TVchannels on subscription.